Does cash money solve energy poverty? Assessing the impact of household heating allowances in Spain. (October 2021) - Barrella, Roberto; Linares, José Ignacio; Romero, José Carlos; Arenas, Eva; Centeno, Efraim
Highlights: Heating allowances usually suffer from design problems that affect their efficacy. We assess the effectiveness of the Thermal Social Allowance in Spain. We apply a bottom-up methodology to model costs for heating and DHW. We propose an alternative aid based on vulnerable households' energy needs. The proposal would decrease winter energy poverty more substantially. Abstract: Energy poverty could be identified as the inability of households to attain a necessitated level of domestic energy services. Since Boardman's pioneering studies, EU Member States have progressively tackled this issue through both mitigating and structural measures. Among the former are the financial aids that seek to support vulnerable households in paying their heating bills. These widespread measures usually suffer from design problems, which can affect their efficacy. That is precisely what this paper aims to provide: an analysis of the effectiveness of the Thermal Social Allowance (TSA) in one of the Member States (Spain), as well as a proposal to redefine it, i.e. the Thermal Energy Cheque (TEC), to address some of its limitations. For that purpose, this paper proposes a bottom-up methodology to characterise Spanish households' theoretical expenditures for heating and domestic hot water. Then, the TEC proposal integrates this methodology in the calculation of an energy cheque that would enhance the current TSA policy. Furthermore, an impact assessment is carried out to evaluate the effectiveness of the two measures in reducing winter energy poverty. The main findings show that in 2019 the limitations in the design of the TSA led to a reduction of winter energy poverty of only 1%, whereas the implementation of the TEC would reduce it by 11%. Nevertheless, both are costly measures that do not tackle other constituent factors of energy poverty, e.g. low energy efficiency of housing, making them unsuitable as medium-long term policies.